Klasyfikacja paliw gazowych = Classification of gaseous fuels - Jasiewicz, Marzena; Nadolna, Marzena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article the distribution of gaseous fuels has been presented. The classification, characteristics and method for determining the flammable gas used by industrial and municipal customers have been described. For individual groups of gases were showed the ways of their acquisition and use. The major components of gaseous fuels and the operational requirements were introduced for each group of gases.
Keywords: paliwa gazowe; rodzina paliw gazowych; grupa paliw gazowych; gaseous fuels; gaseous fuels classification